TINGKAT PEMAHAMAN GURU PJOK TERHADAP KURIKULUM MERDEKA BELAJAR DI SMP SEKECAMATAN KALINYAMATAN JEPARA - Khoirun Nisa', Fitrianti; Slamet Pratama, Dani; Wiyanto, Agus (YLPK Mahardhika, 2024)
Fitrianti Khoirun Nisa'